Dari India untuk Dunia: Peran Darul Ulum Deoband dalam Pelestarian Hadis dan Ulumul Hadis - Masykur Hakim (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2009)
This paper reveals the role of Islamic scholars in India and a significant contribution in Islamic sciences. This paper focuses on the role of Ma’had Darul Ulum Deoband in India. A traditional institution which is a locus of traditions in India and become an institution that seeks to preserve traditions and developing it in the Islamic world through the curriculum, teaching methods, the spread and the productivity of alumni in producing works in hadith.